Implementasi Planning, Organizing, Leading, Controlling (POLC) Program Pelatihan Pengelasan Untuk Meningkatkan Kesiapan Kerja Peserta Didik Lembaga Kursus dan Pelatihan Nusa Citra Indonesia - Fatmawati Fatmawati; Andrie Chaerul; Ahmad Syahid (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the implementation of Planning, Organizing, Leading, Controlling (POLC) in the welding training program to improve the work readiness of students at the Nusa Citra Indonesia course and training institution. This welding training program is organized based on the experience of LKP Nusa Citra Indonesia and the local community's need for training programs that are able to provide expertise or skills that can improve job readiness. This research approach is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. The research subjects consisted of one leader, one manager, one instructor, one student and one graduate of the welding training program of the Nusa Citra Indonesia training and training institute. The analysis of the research obtained shows that (1) the planning of the welding training program is carried out on the basis of identifying community needs to improve work readiness and expertise; (2) the organization is adjusted to the expertise required by the institution; (3) the role of the owner of the institution as a leader to lead and motivate his employees so that the plans that have been prepared run according to the direction and achieve the goals of the institution; (4) supervision is carried out by observing directly or indirectly as well as viewing daily reports on lessons that have been implemented; (5) there are inhibiting factors that hinder students in understanding welding training materials and there are supporting factors that can increase students' work readiness.